Conversational wisdom : strengthening human connection through the power of conversation - Cosgrove, Emily; Hope, Sara (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"Conversation: the heartbeat of our organisations. Right now, we're at risk of losing the art of doing it well. We need to radically change how we talk to each other, to create workplaces where people feel they belong and can thrive. This book will help you understand how to grow your conversational wisdom to create more inclusive and collaborative environments and to make work more meaningful. Conversations carry the greatest potential to impact culture, performance, brand, and engagement. Yet conversation is an under-rated and under-developed skill. Emily Cosgrove and Sara Hope have spent the last 25 years helping people and organisations strengthen human connection through the power of conversation. Drawing from their experience of working with global jewellers to charities, professional services to B-Corporations, they share a wealth of tips, tools, stories, and case studies. Written in a style that is easy to understand, they offer advice on how to get the best out of conversations and get underneath some of the challenges we all face. This is essential reading for learning and development experts, people leaders, coaches and mentors, and HR managers"--
Keywords: Conversation; Organization; BUSINESS & ECONOMICS / Human Resources & Personnel Management; BUSINESS & ECONOMICS / Business Communication / General; BUSINESS & ECONOMICS / Workplace Culture